2017
DOI: 10.5935/1518-0557.20170040
|View full text |Cite
|
Sign up to set email alerts
|

Zika Virus Outbreak - Should assisted reproduction patients avoid pregnancy?

Abstract: Objective: To discuss the requirement from the National Health Surveillance Agency (ANVISA), for assisted reproduction treatment patients to undergo laboratory tests for ZIKV detection, and if the public health authorities and government leaders' recommendations to women simply avoid pregnancy is prudent.Methods: This study was performed in a universityaffiliated in vitro fertilization center in Brazil. We present a critical discussion on the risk of microcephaly due to ZIKV infection and the prevalence of oth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…Dear editor, the publication on Zika virus (ZIKV) outbreak is very interesting. Borges et al . (2017) raised an interesting question: " Should assisted reproduction patients avoid pregnancy ?"…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Dear editor, the publication on Zika virus (ZIKV) outbreak is very interesting. Borges et al . (2017) raised an interesting question: " Should assisted reproduction patients avoid pregnancy ?"…”
mentioning
confidence: 99%
“…(2017) raised an interesting question: " Should assisted reproduction patients avoid pregnancy ?" Borges et al . (2017) concluded that the " ZIKV test before the onset of assisted reproduction treatment does not rule out the risk of the infection during pregnancy " and " In addition, although ZIKV infection risk is extremely high, the microcephaly risk due to ZIKV is not higher than the risk of miscarriage and birth defects due to other recognized pathogens ."…”
mentioning
confidence: 99%